Analisis Sampah Laut Makro Di Kawasan Pariwisata Pantai Mang Kalok, Kabupaten Bangka, Kepulauan Bangka Belitung - Muhammad Arinda Unigraha Utama; Sudirman Adibrata; Kurniawan (Program Studi Akuntansi IKOPIN, 2022)
Marine debris is a problem of aquatic pollution that occurs in many areas today. One of the sectors affected is tourism. This study aims to analyze the type, category, mass, amount, type composition, and density of macro marine debris. The research was conducted at Mang Kalok Beach, Bangka Regency, Bangka Belitung Archipelago from April to May 2018. The data collection method was carried out by purposive sampling with reference to the 2017 Ministry of Environment and Forestry Beach Waste Monitoring Guidelines. Data analysis was carried out using instruments from literature studies. The results showed that all types of macro marine debris can be found on Mang Kalok beach. Waste from organic types in the form of wood and the like, inorganic types in the form of plastic, glass, rubber, metal, cloth, and other types with varied waste categories. The mass and amount of waste in plastic was dominated by 6,545.8 grams and 646 items were found. The largest mass of waste is plastic with a value of 5,484.1 gr. The highest amount of waste is plastic with 315. The composition of the highest type of waste is plastic with 42.2%. The highest density of waste is 63 items/m2. Overall, plastic waste has the highest mass value, quantity, type composition, and density.